ELEVATE SOME TYPES OF ADIPOKINES IN WOMEN WITH POLYCYSTIC OVARY SYNDROME (PCOS) - Alrawi, Nawfal N. R.; Saleh, Ahmed Hamad (PT. Antis International Publisher, 2024)
The current work aimed to estimate some types of Adipokines (Leptin, adiponectin and the resistin) in PCOS women. The participants belong to both PCOS women and healthy women were selected and examined in Azadi teaching hospital at September 2021 to February 2022. 80 patients with 30 controls were used in this study. The current outcomes show the concentration of Leptin in PCOS patients, where concentration of Leptin demonstrated significant (P <0.05) elevate in PCOS women compared with healthy women. Adiponectin concentration in PCOS women indicated significant (P <0.05) reduce compared with healthy women. Resistin concentration in PCOS women indicated significant (P <0.05) raise compared with healthy women. So, based on this findings, PCOS lead to significant (P <0.05) differences in concentration of some types of Adipokines.